Potret Tokoh Trapani “Si Anak Mami” dalam Novel Laskar Pelangi Menurut Teori Psikolanalis Sigmund Freud: Portrait of Trapani “Mama’s Boy” in the novel Laskar Pelangi according to Sigmund Freud's psychoanalysis - Sari, Monica Indah; Rokhmansyah, Alfian (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2023)
According to Sigmund Freud’s psychoanalysis theory, this study aims to reveal the portrait of Trapani, “the mama’s boy,” in the novel Laskar Pelangi. Laskar Pelangi was written by Andrea Hirata in 2006. The literature technique was used to collect data. The collected data were analyzed using Sigmund Freud’s psychoanalysis theory. This novel tells the story of 10 underprivileged Muhammadiyah elementary school students who live in Bangka Belitung. Most of the the students’ parents’ jobs are tin miners. Trapani is a character in Laskar Pelangi. Although Trapani is not the main character in Laskar Pelangi, the character of Trapani, “the mama’s boy,” illustrates the imbalance of three important components in forming personality. The three important components are id, ego, and superego. The result of the research is that Trapani’s id, which is very dependent on his mother, affects his balance of ego and superego. The imbalance of the three important components, namely id, ego, and superego, causes Trapani’s psyche to be disturbed.